Acesso endoscópico transnasal aos tumores selares - Santos, Rodrigo de Paula [UNIFESP] (2006)
Sellar tumor surgery is traditionally a neurosurgeon´s field. However, since the renewed interest in the transseptal-transsphenoidal approach to access the sellar region in the sixties, otolarynngologists have played an important partnership in this procedure. Divulging of endoscopic sinus surgery in otolaryngology created an interest in its application in sellar region surgery. The use of endoscopes allowed a direct transnasal approach to the sphenoidal sinus without need of dissection of the septal mucosa, with less post-operative discomfort and morbidity inferior to that of traditional methods. Objective: The objective of this work was to verify the technical difficulties, intercurrences and post-operative complications in the otolaryngological handling of the endoscopic transnasal approach to the sellar region. Method: The analisys comprised both the files and archive images of 159 patients submitted to sellar region surgery between march 2001 and December 2005, at Universidade Federal de São Paulo / Escola Paulista de Medicina. 91 patients submitted to a total of 95 endoscopic transnasal procedures were included in this study. Results: It was possible to apply the endoscopic transnasal tecnique in all studied patients, independent of age, anatomical variations, tumor characteristics and etyology, and previous surgery history. There was no need of middle turbinate removal, or septal deviations corrections for the surgical procedure in any of the cases. The main intercurrence was the opening of the sellar diaphragm during the removal of the the tumors, causing intra-operative CSF leak in 13.68% of the cases. The post-operative complications encountered were: nasal bleeding (8.42%), CSF leak (8,42%), and meningitis (2.19%). Conclusion: Transnasal endoscopic approach to sellar tumors was done in a minimally invasive form, preserving the nasal structures in the 95 studied procedures, independently of patient age, tumor characteristics and etyology.